Students' Perception of Blended Learning in Cultural Arts Lesson at SMA Pertiwi 1 Padang - Nindi Aulia Safira; Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2024)
The purpose of this study was to determine students' perceptions of blended learning in dance subjects at SMA Pertiwi 1 Padang. The type of research is qualitative with a descriptive method. The research instrument is the researcher himself, assisted by supporting instruments such as stationery and cameras. The data used are primary and secondary data. The data collection techniques were carried out through observation, interviews, literature study, and documentation. The steps for analyzing data in this study are data reduction, data presentation, and conclusion drawing. The results showed that students' perceptions of blended learning in dance lessons were "not good."  In cultural arts lessons in blended learning at SMA Pertiwi 1 Padang, it shows that students prefer face-to-face learning, even though the time allocation is reduced to 2x30 minutes. This is because cultural arts (dance) lessons have more practice than theory. It can be seen from the evaluation indicators in dance learning at SMA Pertiwi 1 Padang in class XI IPS. Students prefer direct or face-to-face learning rather than online learning because cultural arts subjects require more practice than theory. Therefore, learning the blended learning model makes student motivation decrease, so that learning achievement in cultural arts (dance) subjects is less achieved. Students underestimate the learning of cultural arts (dance).